Transcoding unicode characters with AVX‐512 instructions - Clausecker, Robert; Lemire, Daniel (Software, practice & experience, 2023)
Intel includes in its recent processors a powerful set of instructions capable of processing 512‐bit registers with a single instruction (AVX‐512). Some of these instructions have no equivalent in earlier instruction sets. We leverage these instructions to efficiently transcode strings between the most common formats: UTF‐8 and UTF‐16. With our novel algorithms, we are often twice as fast as the previous best solutions. For example, we transcode Chinese text from UTF‐8 to UTF‐16 at more than 5 GiB using fewer than 2 CPU instructions per character. To ensure reproducibility, we make our software freely available as an open‐source library. Our library is part of the popular Node.js JavaScript runtime.